CATALYTIC CONVERSION OF METHANE INTO SYNGAS AND ETHYLENE - Talasbayeva N.S.,; Kazhdenbek B.D.,; Zhang X.L.,; Kaumenova G.N.,; Xanthopoulou G.,; Tungatarova S.A.,; Baizhumanova T.S., (Academic Scientific Journal of Chemistry, 2019)
The object of research is development technology of the new composite materials synthesis for the processing of light alkanes into syngas and ethylene. The study varying technological parameters of the reaction (temperature, volumetric rate, reaction mixture composition) oxidative conversion of methane into syngas and ethylene. Paper presents data of developed methods of synthesis were developed and the catalysts physicochemical characteristics were established. Optimized technological parameters of the process in an integrated automated laboratory setup. It has been established that the active in syngas and ethylene formation in mixture oxidative transformation of CH4+O2+Ar on 10%K-30%Mn-10%Nb/50% glycine catalyst prepared by the SHS (solution combustion synthesis) method and 1.5%K - 3.5%Mn/AlSi catalyst prepared by impregnation method.